Editorial: Peer review and the reviewer’s role – principles and alignments to an effective review - Vinicius Gomes de Vasconcellos (Revista Brasileira de Direito Processual Penal)
Continuing with the analysis of the phases and roles of the scientific editorial process’ actors, this editorial intends to explore the fundamental characteristics of "peer review" and, consequently, of the reviewer in the production of knowledge in scientific journals. Thus, it is intended to analyze the position and role of the reviewer in the scientific editorial process, in order to establish certain important premises for his work and to indicate some guidelines to encourage the improvement of the evaluations. Aiming that purpose, a specific bibliographic reference will be used, grounded on empirical research whenever possible, as well as perceptions of experience as author, reviewer and editor. In this sense, the paper will be structured in three parts: (I) definition and characteristics of peer review; (II) premises of the reviewer’s performance; and, (III) guidelines for consistent review.